Revised energy levels of singly ionized lanthanum. (May 2018) - Güzelçimen, Feyza; Tonka, Mehdi; Uddin, Zaheer; Bhatti, Naveed Anjum; Windholz, Laurentius; Kröger, Sophie; Başar, Gönül
Highlights: Revisal of fine structure levels of singly ionized lanthanum. Hyperfine structure investigation of calibrated Fourier transform (FT) spectra. High accurate determination of the center of gravity wavenumbers. Determination of new magnetic dipole hyperfine structure constants. Abstract: Based on the experimental wavenumbers of 344 spectral lines from calibrated Fourier transform (FT) spectra as well as wavenumbers of 81 lines from the wavelength tables from literature, the energy of 115 fine structure levels of singly ionized lanthanum has been revised by weighted global fits. The classifications of the lines are provided by numerous previous investigations of lanthanum by different spectroscopic methods and authors. For the high accurate determination of the center of gravity wavenumbers from the experimental spectrum, the hyperfine constants of the involved levels have been taken into account, if possible. For the 94 levels with known hyperfine constants the accuracy of energy values is better than 0.01 cm −1 . For 34 levels the magnetic dipole hyperfine constants A have been determined from FT spectra as part of this work. For four of these 34 levels even electric quadrupole hyperfine constants B could be estimated. For levels, which have experimentally unknown hyperfine constants and which are connected only by lines not found in the FT spectra but taken from literature, the uncertainties of energy values are about a factor of 10 higher. A list of all revised level energies together with a compilation of hyperfine structure data is given as well as a list of all lines used.